The Influence of Internal and External Factors on Stock Price Fluctuations in Manufacturing Companies - Fredy Arios Tiblola; Ferdinant Nuru; Harum Putri Prawitaningrum (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
As far as stock prices are concerned, the consideration of both internal and external factors, is very necessary. In this study, we use financial ratios and interest rates as variables to study from 2019 - 2023 the stock prices of manufacturing firms listed on the Indonesia Stock Exchange (IDX). Internal variables investigated here include Return on Assets (ROA), Debt to Equity Ratio (DER) and Earnings Per Share (EPS); while the external variable to be considered is the benchmark interest interest rate. The data used in this study is from the company's own annual reports and internet sources such as Yahoo Finance. A regression model with a Fixed Effect approach took into account both the differences in company characteristics. These analyses shed light on problems such as whether the ROA and EPS affect stock price positive effects at the expense of DER. Instead, we find a significant negative effect on stock prices by benchmark interest rate. The adjusted R² nugget shows that the model is capable of shedding 0.961 units lighter elsewhere in explaining stock price changes. These results are able to help investors and company managers make their market performance related decisions more intelligently by revealing the factors that influence stock price movements.